2019
DOI: 10.1002/eat.23094
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of muscularity‐oriented disordered eating behaviors in U.S. young adults: A prospective cohort study

Abstract: Objective To determine adolescent predictors of muscularity‐oriented disordered eating behaviors in young men and women using a nationally representative longitudinal sample in the United States and to examine differences by sex. Method We used nationally representative longitudinal cohort data collected from baseline (11–18 years old, 1994–1995) and 7‐year follow‐up (18–24 years old, 2001–2002) of the National Longitudinal Study of Adolescent to Adult Health. We examined adolescent demographic, behavioral, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 36 publications
6
34
0
Order By: Relevance
“…Five articles discuss the prevalence and presentation of disordered eating in people of black/African and Indigenous heritage (Marques et al, 2011; Nagata et al, 2019; Striegel‐Moore et al, 2011; Taylor, Caldwell, Baser, Faison, & Jackson, 2007; Tuffa et al, 2020). These articles represent an important start to understanding how disordered eating might present in people with these identities, with the caveat that there are many unique subgroups and experiences within each of these broad racial/ethnic identity groups.…”
Section: Question 1: What Is the Prevalence Of Disordered Eating In Bmentioning
confidence: 99%
“…Five articles discuss the prevalence and presentation of disordered eating in people of black/African and Indigenous heritage (Marques et al, 2011; Nagata et al, 2019; Striegel‐Moore et al, 2011; Taylor, Caldwell, Baser, Faison, & Jackson, 2007; Tuffa et al, 2020). These articles represent an important start to understanding how disordered eating might present in people with these identities, with the caveat that there are many unique subgroups and experiences within each of these broad racial/ethnic identity groups.…”
Section: Question 1: What Is the Prevalence Of Disordered Eating In Bmentioning
confidence: 99%
“…One such tool is the Drive for Muscularity Scale, which represents one’s perception that they are not muscular enough and which was developed and validated by McCreary and Sasse [45]. Drive for muscularity may be a valuable screening tool for identifying men at risk of developing eating disorders or disordered eating behaviors, since 27.5% of adolescent men and 4.9% of young women reported trying to gain weight or build muscle, with 21.9% of men and 4.5% of women exhibiting disordered eating behavior [46]. However, the associated disordered behaviors may not necessarily be associated with restrictive eating patterns or contribute to low energy availability since many of those who reported disordered eating behaviors also reported that they ate more or differently in a manner to gain weight or build muscle [46].…”
Section: Energy Availability Associated With An Initial Working Modelmentioning
confidence: 99%
“…In contrast, the idealized masculine male body image in U.S. popular media and action figures is large and muscular [7]. Nearly one third of adolescent boys in the U.S. report attempts to gain weight or muscle, compared with only 7% of U.S. adolescent girls, findings that have remained relatively stable from 2002 to 2015 [6,8].…”
mentioning
confidence: 99%